Economic analysis of croplivestock integration in the northern Guinea savannah of Nigeria - Ndubuisi, A.; Zeddies, J.; Manyong, Victor M.; Smith, J.M. (2000)
Research was undertaken on the economics of crop-livestock integration in the Northern Guinea Savannah of Nigeria. The aim of the study was to quantify the reciprocal contributions of crops and livestock and also the factors affecting the integration of crops and livestock production in the area. Field data were collected during the 1996/97 farming season from 150 respondents randomly selected at two locations (Zaria and Bauchi) and classified into crop farmers (CF) and crop-livestock farmers (C-LF). The two locations represent different levels of market opportunities. The Zaria area is hypothesized to follow a market-driven path of agricultural intensification while the Bauchi area follows a population-driven path of agricultural intensification. Results of the study showed that the CF in the Zaria area recorded a gross margin (GM) of NGN62,035. This was about three and a half times the GM in Bauchi (NGN17,262). Similarly, the C-LF in the Zaria area recorded a much higher GM (NGN145,334) over that recorded by the C-LF in the Bauchi area (34,367). Among the general factors affecting crop-livestock integration are land, labour, availability of feed, availability of organic and inorganic fertilizer, age and level of education of the farmers. The study concluded that by integrating and using crop-livestock farm linkages, farmers can improve their economic gains more substantially especially in areas with better market opportunities (Zaria). Therefore efforts should be made to substantially improve the market infrastructure and solve some or the problems affecting crop-livestock integration in the NGS of Nigeria.